Kesiapan Mahasiswa Tingkat Akhir dalam Menghadapi Risiko dan Tantangan Dunia Kerja: Studi pada Mahasiswa Universitas Nahdlatul Ulama Kalimantan Barat - Nahuri, Sasinta Bela; Mulyani, Kahar (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the level of readiness of final-year students in facing risks and challenges in the world of work at Nahdlatul Ulama University of West Kalimantan. Using a qualitative approach through case study methods, this research explores the experiences and strategies developed by students in preparing for the transition from academic to professional world. The research sample consisted of final-year students selected through purposive sampling with criteria of having completed at least 90% of total credits. Data collection was conducted through in-depth interviews, participant observation, and document analysis, then analyzed descriptively qualitatively with a thematic approach. The research results identified six main categories of risks faced by students: limited networks, work culture adaptation, financial dependence, lack of soft skills, academic-industry competency gap, and unclear career direction. Each risk category has specific mitigation strategies developed by students, such as networking, internships, taking additional courses, and self-development. Factors affecting readiness include internal factors (personal motivation, self-efficacy, adaptability) and external factors (family support, study program quality, access to industry information). This study recommends strengthening career development programs, improving industry collaboration, developing responsive curricula, strengthening alumni engagement, and implementing comprehensive monitoring and evaluation systems to optimize students' readiness to face the dynamic and competitive world of work.